Case Report: NUTM1-rearranged lung sarcoma: a rare case imaged with dynamic and static 18F-FDG PET/CT - Wumener, Xieraili; Ye, Xiaoxing; Zhao, Jiuhui; Zhang, Yarong; E, Tuya; Zhao, Jun; Liang, Ying (Frontiers in Oncology, 2025)
BackgroundNuclear protein of testis midline carcinoma family member 1 (NUTM1)-rearranged lung sarcomas are rare malignant malignancies. 18F-fluorodeoxyglucose (FDG) positron emission tomography/CT (PET/CT) is widely used for the differential diagnosis and staging of malignant tumours. This study aimed to identify the static and dynamic features of 18F-FDG PET/CT in NUTM1-rearranged lung sarcomas.Case Description: A 46-year-old male patient underwent a chest CT scan for trauma, which revealed a tumor in the hilum of the left lung. The patient also underwent dynamic (chest) and static (whole body) PET/CT scans. The dynamic and static 18F-FDG PET/CT scans showed a tumor in the hilum of the left lung, with a size of 8.6×6.7 cm, an SUVmax of 17.6 and a Ki of 0.0668 ml/g/min. Final pathology and genetic testing confirmed NUTM1-rearranged lung sarcoma.ConclusionsThis case shows dynamic and static 18F-FDG PET/CT and pathological features of NUTM1-rearranged lung sarcomas.